A case of Zimmermann-Laband syndrome with supernumerary teeth - Holzhausen, M.; Goncalves, D.; Correa, F. D.; Spolidório, Luis Carlos [UNESP]; Rodrigues, V. C.; Orrico, SRP (Amer Acad Periodontology, 2003)
Background: Zimmermann-Laband syndrome is a rare autosomal dominant disorder that is characterized by gingival fibromatosis, ear, nose, bone, and nail defects, and hepatosplenomegaly.Methods: This case report describes the clinical presentation and periodontal findings in a 13-year-old female patient with previously undiagnosed Zimmermann-Laband syndrome.Results: Clinical and radiographic findings and genetic counseling confirmed the diagnosis of Zimmermann-Laband syndrome. The most striking oral findings were the presence of gingival enlargement involving both the maxillary and mandibular arches, anterior open bite, non-erupted teeth, and two supernumerary teeth. Periodontal treatment consisted of gingivectomy in four quadrants. Histopathologic evaluation of excised tissue supported the diagnosis of gingival fibromatosis. The patient was referred for appropriate orthodontic treatment and genetic counseling, and has been closely followed for the earliest signs of hepatosplenomegaly.Conclusions: Dental practitioners should be alert for developmental abnormalities that may occur in patients with gingival fibromatosis as this may indicate the presence of a rare disorder like Zimmermann-Laband syndrome. A comprehensive medical history and physical systemic evaluation are essential for correct diagnosis and treatment of these cases.
Keywords: abnormalities, developmental; fibromatosis, gingival; hypertelorism; joint instability; nails, malformed; tooth, supernumerary; Zimmermann-Laband syndrome